2015
DOI: 10.1371/journal.pone.0145659
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Elevated Gene-1 as a Novel Clinicopathological and Prognostic Biomarker for Gastrointestinal Cancers: A Meta-Analysis with 2999 Patients

Abstract: BackgroundThere have been numerous articles as to whether the staining index (SI) of astrocyte elevated gene-1 (AEG-1) adversely affects clinical progression and prognosis of gastrointestinal cancers. Nevertheless, controversy still exists in terms of correlations between AEG-1 SI and clinicopathological parameters including survival data. Consequently, we conducted a comprehensive meta-analysis to confirm the role of AEG-1 in clinical outcomes of gastrointestinal carcinoma patients.MethodsWe performed a compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…27 AEG-1 is upregulated in GC, which is correlated with adverse clinical features and poor prognosis. [28][29][30] Functionally, AEG-1 performes cancer-promoting actions in gastric carcinogenesis and cancer progression, and is involved in multiple aggressive phenotype. [31][32][33][34][35] Yet, as far as we know, there has been no study that has explored the issue of DLGAP1-AS1, miR-628-5p, and AEG-1 in GC.…”
Section: Introductionmentioning
confidence: 99%
“…27 AEG-1 is upregulated in GC, which is correlated with adverse clinical features and poor prognosis. [28][29][30] Functionally, AEG-1 performes cancer-promoting actions in gastric carcinogenesis and cancer progression, and is involved in multiple aggressive phenotype. [31][32][33][34][35] Yet, as far as we know, there has been no study that has explored the issue of DLGAP1-AS1, miR-628-5p, and AEG-1 in GC.…”
Section: Introductionmentioning
confidence: 99%
“…Astrocyte-elevated gene-1 (AEG-1), also known as Metadherin or Lyric, was originally identified as a novel gene induced by human immunodeficiency virus (HIV)-1 or tumor necrosis factor (TNF)-α in primary human fetal astrocytes (PHFA) ( 5 , 6 ). Numerous recent studies have revealed that AEG-1 is markedly overexpressed in various types of human cancer, including hepatocarcinoma, gastrointestinal cancer and malignant glioma ( 7 , 8 ). AEG-1 played an important role in transformation, proliferation, cell survival, evasion of apoptosis, migration and invasion, metastasis, angiogenesis, chemoresistances and epithelial-mesenchymal transition ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, it becomes increasingly hot in the field of tumor research, for the expression level of AEG-1 is abnormally high in various kinds of cancers [2][3][4] while extremely low in normal tissues, which suggests that AEG-1 may involve in tumorigenesis and represent a valuable biomarker. Further, many scientists have proposed that AEG-1 might be a novel prognostic marker on the basis of their investigating the correlation between the expression levels of AEG-1 and tumor samples with different clinical stages, whose studies supported that over-expression of AEG-1 was usually associated with lymph nodes/distant metastasis and a poor prognosis [5][6][7]. Importantly, loss and gain of function studies revealed that AEG-1 involved in multiple signal transduction pathways, and one of the most classic signal pathways was that PI3K-Akt and GSK-3β acted on Ha-ras to activate c-Myc, which subsequently induced AEG-1 to over-express and contributed to AEG-1 exerting its oncogenic properties [8].…”
Section: Introductionmentioning
confidence: 99%